Sponsored links: Algebra eBooks
 

Related

linsolve

eq1:4*x-2*y+z=-1;

eq2:x+y+z=2;

eq3:9*x+3*y+z=-16;

Calculate

linsolve

eq1:x*4+y-2=y^2;

eq2:x^(1/2)+2=y;

linsolve([eq1,eq2],[x...

Calculate

linsolve

eq1:f(x)=a*x+b;

eq2:f(x+1)-f(x);

linsolve([eq1,eq2],[x...

Calculate

linsolve

eq1:0.21=R1+(w0^2*M^2...

eq2:0.81172=R1+(w1^2*...

eq3:2.0207=R1+(w2^2*M...

Calculate

linsolve

eq1:0=K1*Brr-K2*Br*HH...

linsolve([eq1],[Br]);

Calculate

linsolve

eq1:Ov+Oo=0;

eq2:k1*Cco*Co-k1r*Cco...

linsolve([eq1,eq2],[O...

Calculate

linsolve

eq1:4*x+3*y=5;

eq2:8*x+6*y=10;

linsolve([eq1,eq2],[x...

Calculate

linsolve

jednacine: [x+y=30, 2...

promenljive: [x,y];

odziv: linsolve(jedna...

Calculate

linsolve

eq1:a+b+c=0;

eq2:d+5-b=0;

eq3:f-d-5-e=0;

Calculate

linsolve

eq1:x=g*(a+b);

eq2:y=g*(a+(1-w)*c);

eq3:z=g*(a+(1-w*w)*c);

Calculate

linsolve

Run Example
(%i1)eq1:y*(t/2)^2+z=-(t/2)^4;
                                     2        4
                                    t  y     t
(%o1)                           z + ---- = - --
                                     4       16
(%i2) eq2:x*(d/2)^2+y*(h/2)^2+z=-((d/2)^2+(h/2)^2)^2;
                             2      2         2    2
                            h  y   d  x      h    d  2
(%o2)                   z + ---- + ---- = - (-- + --)
                             4      4        4    4
(%i3) eq3:x*R^2+z=-R^4;
                                   2          4
(%o3)                           x R  + z = - R
(%i4) linsolve([eq1,eq2,eq3],[x,y,z]);
            2      4    4      2  2    4        2  4    2  4
           t  (16 R  - h  - 2 d  h  - d ) - 16 h  R  + h  t
(%o4) [x = -------------------------------------------------, 
                         2  2    2     2       2
                     16 h  R  + t  (4 d  - 16 R )
            2  4      4  2      2  2  2      4  2    4   2      2
      - 16 d  R  + 4 h  R  + 8 d  h  R  + 4 d  R  + t  (d  - 4 R )
y = - ------------------------------------------------------------, 
                          2  2    2     2       2
                      16 h  R  + t  (4 d  - 16 R )
       2     2  4    4  2      2  2  2    4  2     2  4  2
      t  (4 d  R  - h  R  - 2 d  h  R  - d  R ) + h  t  R
z = - ----------------------------------------------------]
                      2  2    2     2       2
                  16 h  R  + t  (4 d  - 16 R )
(%i5) 
Run Example
eq1:i1=i2;
(%o1)                               i1 = i2
(%i2) eq2:i2=i3+i4;
(%o2)                            i2 = i4 + i3
(%i3) eq3:i4+i6=i7;
(%o3)                            i6 + i4 = i7
(%i4) eq4:i5=i6;
(%o4)                               i5 = i6
(%i5) eq5:v1=ug;
(%o5)                               v1 = ug
(%i6) eq6:i2=(v1-v2)/r1;
                                      v1 - v2
(%o6)                            i2 = -------
                                        r1
(%i7) eq7:i3=v2/r3;
                                         v2
(%o7)                               i3 = --
                                         r3
(%i8) eq8:i4=(v2-v3)/r2;
                                      v2 - v3
(%o8)                            i4 = -------
                                        r2
(%i9) eq9:v4=a*v2;
(%o9)                              v4 = a v2
(%i10) eq10:i6=(v4-v3)/r4;
                                      v4 - v3
(%o10)                           i6 = -------
                                        r4
(%i11) eq11:i7=v3/r5;
                                         v3
(%o11)                              i7 = --
                                         r5
(%i12) res:linsolve([eq1,eq2,eq3,eq4,eq5,eq6,eq7,eq8,eq9,eq10,eq11],[i1,i2,i3,i4,i5,i6,i7,v1,v2,v3,v4]);
(%o12) [i1 = ((r3 (a r5 - r5 - r4) - r4 r5 + r2 (- r5 - r4)) ug)
/(r1 (r3 (a r5 - r5 - r4) - r4 r5 + r2 (- r5 - r4))
 + r3 (r2 (- r5 - r4) - r4 r5)), i2 = ((r3 (a r5 - r5 - r4) - r4 r5
 + r2 (- r5 - r4)) ug)/(r1 (r3 (a r5 - r5 - r4) - r4 r5 + r2 (- r5 - r4))
 + r3 (r2 (- r5 - r4) - r4 r5)), i3 = - ((r2 (r5 + r4) + r4 r5) ug)
/(r1 (r3 (a r5 - r5 - r4) - r4 r5 + r2 (- r5 - r4))
 + r3 (r2 (- r5 - r4) - r4 r5)), i4 = (r3 (a r5 - r5 - r4) ug)
/(r1 (r3 (a r5 - r5 - r4) - r4 r5 + r2 (- r5 - r4))
 + r3 (r2 (- r5 - r4) - r4 r5)), i5 = - (r3 (a r5 - r5 + a r2) ug)
/(r1 (r3 (a r5 - r5 - r4) - r4 r5 + r2 (- r5 - r4))
 + r3 (r2 (- r5 - r4) - r4 r5)), i6 = - (r3 (a r5 - r5 + a r2) ug)
/(r1 (r3 (a r5 - r5 - r4) - r4 r5 + r2 (- r5 - r4))
 + r3 (r2 (- r5 - r4) - r4 r5)), i7 = - (r3 (r4 + a r2) ug)
/(r1 (r3 (a r5 - r5 - r4) - r4 r5 + r2 (- r5 - r4))
 + r3 (r2 (- r5 - r4) - r4 r5)), v1 = ug, 
v2 = - (r3 (r2 (r5 + r4) + r4 r5) ug)/(r1
 (r3 (a r5 - r5 - r4) - r4 r5 + r2 (- r5 - r4))
 + r3 (r2 (- r5 - r4) - r4 r5)), v3 = - (r3 (r4 r5 + a r2 r5) ug)
/(r1 (r3 (a r5 - r5 - r4) - r4 r5 + r2 (- r5 - r4))
 + r3 (r2 (- r5 - r4) - r4 r5)), v4 = - (r3 (a r2 (r5 + r4) + a r4 r5) ug)
/(r1 (r3 (a r5 - r5 - r4) - r4 r5 + r2 (- r5 - r4))
 + r3 (r2 (- r5 - r4) - r4 r5))]
(%i13)  res[10];
(%o13) v3 = - (r3 (r4 r5 + a r2 r5) ug)
/(r1 (r3 (a r5 - r5 - r4) - r4 r5 + r2 (- r5 - r4))
 + r3 (r2 (- r5 - r4) - r4 r5))
(%i14) 
Run Example
eq1:2*X+Y+Z=191.11;
(%o1)                        Z + Y + 2 X = 191.11
(%i2) eq2:X+2*Y+3*Z=693.73,eq3:X-3*Y-4*Z=-643.4;
(%o2)                       3 Z + 2 Y + X = 693.73
(%i3) linsolve([eq1,eq2,eq3],[X,Y,Z]);

rat: replaced -191.11 by -19111/100 = -191.11

rat: replaced -693.73 by -69373/100 = -693.73
(%o3)                                 []
(%i4) 

Related Help

Help for Linsolve